MISSION BERLIN--A Mobile Gamified Exploration of a New Educational Landscape - Pardoel, Bart; Papadima-Sophocleous, Salomi; Athanasiou, Androulla (My University, 2019)
Although the use of games and game elements other than pure entertainment has been studied in several academic fields, studies on completely gamified courses for foreign language learning in secondary schools are still scarce. This exploratory research paper contributes to a better understanding of the affordances of mobile gamification in Foreign Language (FL)/L2 education, specifically in the context of a Dutch secondary school. A technology-assisted mobile gamified language course for A1 German as an FL (GFL), called MISSION BERLIN, was developed, implemented, and evaluated. The students assumed the role of secret agents on a six-week mission to Germany’s capital, using the official Moodle app on their own devices. A total number of 45,003 student’s interactions (clicks) with the Moodle software were recorded and analysed, including the total number of individual interactions and the times when the clicks were made. In addition, the way how students collected the coins was analysed, making it possible to identify students’ playing patterns and to explore different student actions.
Keywords: Foreign language learning; gamification; Moodle; MALL